The effectiveness of google classroom in teaching English during Covid-19 at SMA N 1 M. Payed - Irma Dewi Isda; Imran Imran; Purwati Purwati; Rahmiati Rahmiati (Universitas Islam Malang, 2021)
This research aimed to find out Google Classroom effectiveness, which was used to enhance students’ speaking skill. This research used a quasi-experimental with a pre-experimental research design. The subject of this study is the eleventh grade of senior high school at SMA N 1 M. Payed. It involved 25 students as a sample of this study. In the process of data collection, the researcher used a pre-test and post-test. The researcher analyzed the data using Wilcoxon Ranks Test to test the hypothesis. This study found the value of significance (2-tailed) was lower than the significance level (0.000 < 0.05), then the Ha was accepted. It means there was a significant value on students’ achievement of the speaking skill by using Google Classroom. Finding obtained of pretest 71,20 and posttest 78,16. In conclusion, the mean pretest and posttest scores differ significantly, or there is an effect of using google classroom enhancing students speaking skill at SMA N 1 Manyak Payed. However, it can be concluded that Google Classroom significantly affects students’ speaking skill and helps them finish and collect the assignment without any bound by time and space.Keywords: google classroom; teaching English; Covid-19